We have never been woke: the cultural contradictions of a new elite - al-Gharbi, Musa (Princeton University Press, 2024)
How a new “woke” elite uses the language of social justice to gain more power and status—without helping the marginalized and disadvantagedSociety has never been more egalitarian—in theory. Prejudice is taboo, and diversity is strongly valued. At the same time, social and economic inequality have exploded. In We Have Never Been Woke, Musa al-Gharbi argues that these trends are closely related, each tied to the rise of a new elite—the symbolic capitalists. In education, media, nonprofits, and beyond, members of this elite work primarily with words, ideas, images, and data, and are very likely to identify as allies of antiracist, feminist, LGBTQ, and other progressive causes. Their dominant ideology is “wokeness” and, while their commitment to equality is sincere, they actively benefit from and perpetuate the inequalities they decry. Indeed, their egalitarian credentials help them gain more power and status, often at the expense of the marginalized and disadvantaged.We Have Never Been Woke details how the language of social justice is increasingly used to justify this elite—and to portray the losers in the knowledge economy as deserving their lot because they think or say the “wrong” things about race, gender, and sexuality. Al-Gharbi’s point is not to accuse symbolic capitalists of hypocrisy or cynicism. Rather, he examines how their genuine beliefs prevent them from recognizing how they contribute to social problems—or how their actions regularly provoke backlash against the social justice causes they champion.A powerful critique, We Have Never Been Woke reveals that only by challenging this elite’s self-serving narratives can we hope to address social and economic inequality effectively